Diseño de un plan de mercadeo para la empresa FC Power Solutions S.A.S. (2019)
In this document a marketing plan was made for the company FC POWER SOLUTIONS SAS. For this an in-depth investigation was carried out to collect all the important information concerning the marketing and more specifically the marketing plan. Based on the research carried out the marketing plan for the company under study was carried out in the following steps: diagnosis of the current situation of the company, SWOT matrix, marketing objectives, marketing strategies, marketing programs, marketing schedule, financial study and monitoring indicators for the evaluation of the resulting marketing plan.